UNDERSTANDING EFL STUDENTS' DEPENDENCY ON CHATGPT IN ENGLISH LANGUAGE LEARNING: EVIDENCE FROM INDONESIAN HIGHER EDUCATION - Dakhi, Epos Sister Krismon Selan; Muchlas Suseno; Samsi Setiadi (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2025)
This study investigates the growing dependency of Indonesian EFL students on ChatGPT in the context of English language learning. Using a qualitative descriptive design, data were gathered from learning journals and semi-structured interviews involving nine undergraduate students across three universities. Thematic analysis revealed that students widely perceived ChatGPT as a valuable tool for enhancing writing, vocabulary, and confidence. However, its frequent use led to behavioral and emotional dependency. Factors contributing to this dependency included ease of access, low linguistic self-efficacy, academic pressure, and perceived AI authority. Notably, dependency correlated with reduced engagement in traditional learning strategies, diminished critical thinking, and limited learner autonomy. While ChatGPT offers substantial educational benefits, its overuse raises concerns about passive learning and cognitive disengagement. The findings highlight the need for pedagogical strategies that foster critical AI literacy and promote balanced use. This study contributes to the growing discourse on ethical and effective AI integration in language education